PENGARUH RETURN SAHAM, ASSETS TURNOVER, LEVERAGE, DAN PRICE TO BOOK VALUE TERHADAP DEVIASI ACTUAL GROWTH RATE DARI SUSTAINABLE GROWTH RATE - Hesty Erviani Zulaecha; Dewi Rachmania; Mohamad Zulman Hakim; Sri Utami (COMPETITIVE, 2020)
The purpose of this study was to determine the effect of stock returns, asset turnover, leverage, and price to book value to the deviation of the actual growth rate of sustainable growth rates in manufacturing companies on the Indonesia Stock Exchange (IDX). The time period of the study is 4 years, namely the period 2015-2018. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The sampling technique uses purposive sampling technique. Based on the established criteria obtained by 17 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis.The results showed that stock returns, asset turnover, and leverage significantly positive effect on the deviation of the actual growth rate of the sustainable growth rate, price to book value had a significant negative effect on the deviation of the actual growth rate of the sustainable growth rate, and stock returns, asset turnover,leverage , and price to book value together affect the actual growth rate deviation from the sustainable growth rate.